2022
DOI: 10.3390/antiox11020230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Colchicine in a Rat Model of Diet-Induced Hyperlipidemia

Abstract: Inflammation and hyperlipidemia play an essential role in the pathophysiology of endothelial dysfunction as well as atherosclerotic plaque formation, progression and rupture. Colchicine has direct anti-inflammatory effects by inhibiting multiple inflammatory signaling pathways. The purpose of our study was to evaluate colchicine activity in an animal model of hyperlipidemia induced by diet. A total of 24 male rats (wild type, WT) were divided into three groups: group one fed with a basic diet (BD) (WT + BD, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…Excess cholesterol caused several diseases including atherosclerosis ( Hall, 2016 ), infertility ( Mahdavi et al., 2021 ) and toxicity in different organs as the liver ( Yu et al., 2021 ), thyroid gland ( Rasekh et al., 2021 ) and kidney ( Kaur et al., 2021 ). Zălar et al. (2022) reported that rats-fed a high-fat diet for 4 weeks showed an increase in oxidative stress, pro-inflammatory markers as well as induced signs of endothelial dysfunction in aorta sections.…”
Section: Introductionmentioning
confidence: 99%
“…Excess cholesterol caused several diseases including atherosclerosis ( Hall, 2016 ), infertility ( Mahdavi et al., 2021 ) and toxicity in different organs as the liver ( Yu et al., 2021 ), thyroid gland ( Rasekh et al., 2021 ) and kidney ( Kaur et al., 2021 ). Zălar et al. (2022) reported that rats-fed a high-fat diet for 4 weeks showed an increase in oxidative stress, pro-inflammatory markers as well as induced signs of endothelial dysfunction in aorta sections.…”
Section: Introductionmentioning
confidence: 99%
“…4J and 4K Attenuated HFD-Induced AST and ALT Levels. HFD is known to alter liver functions and can cause fatty liver disease; 27 we therefore measured aspartate aminotransferase (AST) and alanine transaminase (ALT) levels. As expected, the disease group and SIM-treated group showed prominent increase in AST and ALT levels indicating liver dysfunction.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Animal studies showed that colchicine reduces the inflammatory response and enhances the antioxidant capacity in rats fed with a high-fat diet [ 31 ]. In addition, colchicine treatment induced a protective effect on oxidative stress, the antioxidant redox system, and Ca2 released in serum and polymorphonuclear leucocytes of familial Mediterranean fever patients in remission that are characterized by oxidative stress [ 32 ]. Thus, colchicine treatment could induce a protective effect on diabetic risk via a regulatory effect on inflammatory processes and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%